Chemical constituents from the roots of Cichorium glandulosum Boiss. et Huet (Asteraceae). (June 2021) - Wang, Ru; Zheng, Guijuan; Dang, Ting; Jin, Pengfei; Yao, Jia; Su, Linjie; Yao, Guangmin; Qin, Dongmei
Abstract: A phytochemical investigation of the roots extract of Cichorium glandulosum led to the isolation and characterization of fourteen compounds, including five sesquiterpene lactones (1 –5 ), five flavonoids (6 –10 ), and four lignans (11 –14 ). Their structures were determined by spectroscopic data analysis and comparison with the literatures. This is the first report of the crystal data of lactucopicrin (1 ). This is the first time to report the isolation of 6, 8, 11- epi -desacetylmatricarin (2 ), desacetylmatricarin (3 ), ixerisoslde C (4 ), magnodelavin (5 ), 2ʹ, 4-dihydroxy-4ʹ-methoxy-6ʹ- O - β -glucopyranoside dihydrochalcone (6 ), (−)-evofolin B (7 ), isoquercitrin (8 ), myricetin 7-methyl-ether-3- O -glucoside (9 ), (+)-medioresinol (12 ), 4- O -methylcedrusin [2-(3ʹ, 4ʹ-dimethoxyphenyl)-3-hydroxymethyl-2, 3-dihydro-7-hydroxybenzofuran-5-propan-1-ol] (13 ), and (2 R, 3 S )-samwirin A (14 ) from C. glandulosum . Among them, compounds 5, 9, 13, and 14 were obtained from Asteraceae family for the first time. The chemotaxonomic significance of all the isolates 1 –14 was discussed. Graphical abstract: Image 1 Highlights: Fourteen compounds were isolated from the roots of Cichorium glandulosum. This is the first report of the crystal data of lactucopicrin (1 ). Compounds 2 –9 and 12 –14 were obtained from the genus of Cichorium for the first time. Compounds 5, 9, 13, and 14 were isolated from Asteraceae family for the first time. The chemotaxonomic significance of all the isolates was discussed.